Film cooling by means of one-row inclined holes arranged in dimples - Khalatov, A.A.; Borisov, I. I.; Dashevsky, Y.Y.; Pachomov, M.A.; Terechov, V. I. (Reports of the National Academy of Sciences of Ukraine, 2015)
The comparative experimental study of a flat plate film cooling by means of inclined holes arranged in dimples having the "crater" or trench shape is presented. As shown, these configurations enable one to increase significantly the cooling and to reduce its spanwise non-uniformity as compared to the traditional configuration of inclined holes. These advantages appear remarkably at the higher blowing parameters.